Literature Review Gaya Belajar untuk Berpikir Kritis dan Hasil Belajar Siswa - Teguh Famuji; Sunarti Sunarti (Proceedings Series on Social Sciences & Humanities, 2022)
The purpose of this literature review is to identify student learning models to increase critical thinking and student learning outcomes. The results of the literature review show that the learning model is able to optimize critical thinking and student learning outcomes. Educators must optimize choosing learning models to think critically and get optimal learning outcomes. The learning model using a scientific approach can encourage students to think critically. Through the model of Problem based learning, Project Based Learning, Inquiry as a learning model.